Efficacy of Extracorporeal Shockwave Therapy on Calcified and Noncalcified Shoulder Tendinosis: A Propensity Score Matched Analysis. (14th March 2019) - Wu, Kuan-Ting; Chou, Wen-Yi; Wang, Ching-Jen; Chen, Chen-Yu; Ko, Jih-Yang; Chen, Po-Cheng; Cheng, Jai-Hong; Yang, Ya-Ju
Abstract : Background . Extracorporeal shock wave therapy (ESWT) had been proved to be beneficial in calcific tendinosis; however, the treatment efficacy in noncalcific tendinosis of rotator cuff still remains controversial. The present study was to compare the outcomes ESWT among the noncalcific rotator cuff tendinosis and different types of calcific tendinosis on the basis of similar shoulder functional status. Methods . A retrospective, comparative study was conducted with the enrollment of 20 patients in each group through propensity score matching in a 1:1:1 ratio from 291 patients who underwent single ESWT for painful shoulder tendinosis. The patients were divided into three groups which included noncalcified tendinosis (NCTS), type I dense calcified tendinosis of shoulder (DCTS), and type II and type III translucent calcified tendinosis of shoulder (TCTS) according to Gartner and Heyer classification. The clinical evaluation included the subjective pain score with visual analog scale (VAS) and functional outcome with Constant and Murley score (CMS). Results . Twelve months after ESWT, the VAS in TCTS (1.5 ± 2.48) was statistically significant lower than NCTS (2.9 ± 2.86) and DCTS (3.8 ± 2.46) (p=.011). For the functional outcome, the overall CMS was superior in TCTS than the NCTS and DCTS (86.9 ± 19.7 versus 78.7 ± 18.3 and 71.1 ± 17.8, p=.014). Besides, the subscales of pain score, strength, and range of motion in TCTS improved significantly better than NCTS and DCTS. 70% of patients were complaint-free in TCTS group, which was higher than the NCTS group (15%) and DCTS group (25%) (p<0.05). Conclusion . The present study indicated that the high-dose ESWT posed superior clinical efficacy in type II/III calcification tendinosis rather than type I calcification and noncalcific shoulder tendinosis.